Pengaruh Model Pembelajaran Mandiri Tipe Savi (Somatic, Auditory, Visualization, Intellectually) terhadap Kemandirian dan Minat Belajar Santri pada Pembelajaran Fiqh Kelas VIII di MTsS PPMTI Bayur - Elvira Mulia; Wedra Aprison; Supratman Zakir; Zulfani Sesmiarni (Departement of Mathematics Education, 2023)
The purpose of this study was to determine the effect of the SAVI type self-learning model on student independence and interest in learning Fiqh. The method used in this study was a Quasi Experiment with the design of The Static Group Comparison Randomized Control Group Only Design by applying the SAVI type independent learning model (Somatic, Auditory, Visualization, Intellectualy) in the experimental class of 27 people and 28 people in the control class. Research data on student independence and learning interest were collected by means of a questionnaire, then analyzed by using the Manova test with the help of SPSS version 22. The findings of this study were hypothesis testing (1) There was an influence of the SAVI type independent learning model (Somatic, Auditory, Visualization, Intellectually) on student learning independence in the subject of Fiqh at MTsS PPMTI Bayur. Obtained from a significance value smaller than 0.05, namely 0.000 <0.05. (2) There is an influence of the SAVI type independent learning model (Somatic, Auditory, Visualization, Intellectualy) on students' learning interest in the Fiqh subject at MTsS PPMTI Bayur. Obtained from a significance value smaller than 0.05, namely 0.000 <0.05. (3) There is an influence of the SAVI type independent learning model (Somatic, Auditory, Visualization, Intellectualy) on student independence and interest in learning Fiqh at MTsS PPMTI Bayur. Obtained from a significance value smaller than 0.05, namely 0.000 <0.05 with the result F_count = 27.432 with F_table = 3.40 (F_count>F_table).